(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3aj GdecGSH GdeMQeI, dG jNai Cfge bSehG GdecGSH HGYJHGQ eG jWQC YdjgG ef GdCMcGe GdNeSI Edi CQHYI CbSGe; MQGe heSJMH hecQhg heHGMs
(3BNQgG (B:s
(3BNQgG(B: (3cGf jfHZj Cf jbGd dGSJdGe Pdc hbhY GdJRGMe aj fGUjI GdedcjI Hjf GdeGdc GdCUjd hGdeTJQj GdChd dCf GdeaQhV gh HbGA edcjI GdeGdc GdCUdj Edi (B.. (3GdYbO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs